Conversion of Waste into Wealth: A Study in Solid Waste Management - T. Janakiram; K. Sridevi (E-Journal of Chemistry)
Disposal of solid waste has been the talk of the day. An attempt has been made to dispose of the solid waste Jatropha (Kattamanakku). Aerobic composting method was employed. Properly treated solid wastes of different composition were mixed with slurries of cowdung and physicochemical parameters were measured after 30 and 60 days of composting. It was observed that percentages of nitrogen, phosphorous, potassium, sodium, calcium and magnesium increased as time elapsed. Water holding capacity, electrical conductivity and moisture content were found to increase, while pH and C/N ratio have been observed to decrease.